(Re)presentation of dental wear for ethical consideration: Analysis of a digital how‐to guide. (11th June 2022) - Lagan, Emma M.
Abstract: Objectives: Using photographs of human remains, including bones and teeth, in publications may have unethical implications when considering descendant communities. In the United States, many museums in deference to agreement with descendent communities prohibit publication of photos. In order to convey specific information to audiences and respect the wishes of descendent communities, authors should turn to digital illustrations, where appropriate. This article seeks to demonstrate that, regardless of skill or experience with digital illustration software, this technique is accessible to all researchers. Materials and Methods: Forty participants completed a tutorial on digitizing a mandibular molar with wear and caries. Each participant was provided the same base image and instructions. Participants had various levels of experience with (1) human remains, (2) dentition, and (3) digital illustration software. All participants used the opensource freeware program, Krita. Results: A majority of participants (75%) took 30 to 90 min to complete the exercise; 25 illustrations were produced and showed strong similarities in occlusal outline, occlusal fissures, and dentine exposure. There was a 3.56% (± 0.93%) discrepancy in total tooth outline between participants' outlines ( n  = 23) and the author's reference image. The average participant satisfaction with their final image was 3.73 (out of 5), and the average user‐friendly rating was 4.2 (out of 5). Discussion: The consistency of illustrations across participants, as well as the satisfactory self‐ratings, demonstrates that digital illustrations, regardless of experience with illustration programs, are accessible to researchers. As a result, more authors should consider replacing photographs of human remains with digital illustrations in publications. While this technique can, and should, be used across any population, the implementation may be one step along a path of a more inclusive anthropology.